The Influence of Discipline on Students' Work Readiness In Muhammadiyah Playen Vocational Secondary Schools With Knowledge As An Intervening Variable - Trihantoro*, Yunanto Andang; Santosa, Budi; Susatya, Edhy (Riwayat: Educational Journal of History and Humanities, 2024)
Schools are one of the formal institutions that play an important role in society in realizing Indonesia's national education goals, providing programs and activities that can help students develop their abilities in both academic and non-academic fields. This type of research is quantitative research that uses primary data collected randomly from students at the Muhammadiyah Playen Vocational School using a questionnaire as a data collection technique which is distributed via G-Form. The data collected consisted of 221 respondents, with details of 155 students and 66 female students. The estimation method used in this research is multiple linear regression which is processed using the IBM SPSS Statistics 25 application. The results of the research show that the results of the analysis conclude that, (1) discipline (X) is proven to influence knowledge (Y) at the Muhammadiyah Playen Vocational School influence of 0.594, (2) knowledge (Y) is proven to have an effect on work readiness (Z) with an effect size of 0.279, and (3) discipline (X) has an indirect effect on work readiness (Z) of 0.115 using knowledge (Y) as an intervention variable. However, based on model 3, the magnitude of the influence of discipline will be greater if it directly affects work readiness, namely 0.553 compared to the intervening variable knowledge (Y).